2002
DOI: 10.1177/154405910208100806
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Properties of Human Dental Pulp Stem Cells

Abstract: In this study, we characterized the self-renewal capability, multi-lineage differentiation capacity, and clonogenic efficiency of human dental pulp stem cells (DPSCs). DPSCs were capable of forming ectopic dentin and associated pulp tissue in vivo. Stromal-like cells were reestablished in culture from primary DPSC transplants and re-transplanted into immunocompromised mice to generate a dentin-pulp-like tissue, demonstrating their self-renewal capability. DPSCs were also found to be capable of differentiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
1,555
2
130

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,798 publications
(1,772 citation statements)
references
References 24 publications
42
1,555
2
130
Order By: Relevance
“…They contain progenitor/stem cells that can differentiate into dentin-forming odontoblasts and maintain the homeostasis of dental mineralized tissue by polarization and secretion of predentindentin components, in response to the appropriate stimuli, e.g. caries, chemicals or trauma (Tonomura et al 2007;Gronthos et al 2002). Researches indicated that DPCs whether from human, pigs or rats were recognized as a source of mesenchymal stem cells (Yang et al 2007;Zhang et al 2005;Alliot-Licht et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They contain progenitor/stem cells that can differentiate into dentin-forming odontoblasts and maintain the homeostasis of dental mineralized tissue by polarization and secretion of predentindentin components, in response to the appropriate stimuli, e.g. caries, chemicals or trauma (Tonomura et al 2007;Gronthos et al 2002). Researches indicated that DPCs whether from human, pigs or rats were recognized as a source of mesenchymal stem cells (Yang et al 2007;Zhang et al 2005;Alliot-Licht et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…No tooth extraction was needed and explants, derived from the alveolar crestal and horizontal fibers of PDL, allowed the migration of a population ofMSCs, all showing the same morphological and phenotypical features previously described (25)(26). The evaluation under contrast phase light microscopy of ex-vivo expanded PDL-MSCs cultured with osteogenic medium after 3 and 4 weeks showed the…”
Section: Resultsmentioning
confidence: 63%
“…49 Bir farenin immun sistemi baskılanarak sırtına transplante edilen dental pulpa kök hücrelerinin dentin-pulpa kompleksine benzer bir yapı oluşturduğu izlenmiştir. [50][51][52][53] Düşen süt dişleri, kök hücre çalışmalarında etik açıdan bir sorun olmadan kullanılabilmektedir-ler. 37,38,43,44,[54][55][56] Bu hücrelerin osteoblastlar, odontoblastlar, adipositler, kondrositler, ve hepatositler gibi çeşitli hücre tiplerine (in vitro ve in vivo) diferansiye olma yeteneğine sahip olduğu gösterilmiştir.…”
Section: Dental Kök Hücrelerunclassified
“…12 Yetişkinlerde kök hücre sayısı azaldığı için neredeyse kök hücrelere hiç rastlanmaz. 23,24 Embriyonik kök hücrelerin farklılaşma yeteneğinin fazla olması, bu hücreleri daha değerli kılmaktadır. 18 Ancak embriyonik kök hücrelerin elde edilmesindeki etik ve yasal tartışmalar ve tümör oluşma riski vardır.…”
unclassified